2020
DOI: 10.1016/j.clae.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and repeatability of four different devices to measure non-invasive tear breakup time (NIBUT)

Abstract: Purpose: Since tear film stability can be affected by fluorescein, the International Dry Eye Workshop (DEWSII) recommended non-invasive measurement of tear breakup time (NIBUT). The aim of this study was to investigate the agreement and repeatability of four different instruments in the measurement of NIBUT.Methods: 72 participants (mean 24.2 ± 3.6 years) were recruited for this multi-centre, cross-sectional study. NIBUT was measured three times from one eye using each of the instruments in randomized order on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…Automated objective measures of NIBUT have been studied with other instruments, such as the Keratograph 5 M (Oculus) [5-9, 15, 16] and RT7000 (Tomey) [9], showing shorter values than conventional subjective measures provided by examiners using fluorescein [5,8,15,17]. Recently, the clinical usefulness of NIBUT measures obtained with an automated device (Sirius topography, CSO) has been also investigated [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Automated objective measures of NIBUT have been studied with other instruments, such as the Keratograph 5 M (Oculus) [5-9, 15, 16] and RT7000 (Tomey) [9], showing shorter values than conventional subjective measures provided by examiners using fluorescein [5,8,15,17]. Recently, the clinical usefulness of NIBUT measures obtained with an automated device (Sirius topography, CSO) has been also investigated [7].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, no significant differences were obtained between consecutive measures, as well as a low intrasession variability (less than 1 s) and clinically acceptable ranges of agreement between measures (as maximum 3.5 s). Other devices, such as the Placido-disk-based system Keratograph 5 M, have shown contradictory results depending on the study, with authors showing no differences between repeated measures [5,8], and other authors finding significant differences between measures of NIBUT during the same day [15,16]. Differences between studies in the level of consistency of repeated NIBUT measures could be explained by differences in terms of the waiting time between them.…”
Section: Depending On the Methodology Or Device Used As Well As Depending On The Sample Evaluated Tmh Values Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A cold light source usually refers to a light external to a microscope that allows diffuse illumination without marked thermal impact on the sample. It can be used to observe the stability of the tear film (usually in the form of a placido pattern), the tear meniscus and the lipid thickness (through interferometric patterns) [197]. Instruments can be used as stand-alone, some with digital imaging and objective software analysis [198], or in conjunction with a slit lamp biomicroscope for control and magnification.…”
Section: Cold Light Illuminationmentioning
confidence: 99%
“…A change in the edges of the mires reflects compromised tear film integrity. Bandlitz et al demonstrated that there is agreement and repeatability of measure between subjective and objective devices [11], while Lee et al demonstrated that the agreement between the results extrapolated from two different instruments (Tomey RT-7000 Auto Refractor-Keratometer and Oculus Keratograph) was poor [12]. The Keratograph 5 M (Oculus Optikgeräte GmbH, Wetzlar, Germany) allows the measure of quantitative values, such as the NIBUTf, which is the initial tear film breakup, whereas the NIBUTav represents the average of all tear film breakups occurring over the entire cornea.…”
Section: Noninvasive Tear Break-up Timementioning
confidence: 99%